Frontiers in polar biology in the genomic era (National Academies Press, 2003)
The report highlights research areas in polar biology that can benefit from genomic technologies and assesses the impediments to the conduct of polar genomic research. It also emphasizes the importance of ancillary technologies to the successful application of genomic technologies to polar studies. The report recommends the development of a new initiative in polar genome sciences that emphasizes collaborative multidisciplinary research to facilitate genome analyses of polar organisms and coordinate research efforts.